Tied Up in Nots over Genetic Parentage - Johnston, Josephine (The Hastings Center report, 2007)
Because an influenza pandemic would create the most serious hardships for those who already face most serious hardships, countries should take special measures to mitigate the effect of a pandemic on existing social inequalities. Unfortunately, there is little evidence that anybody is thinking about that.